2015
DOI: 10.1016/j.cub.2014.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Serotonin Release Triggers the Heat Shock Response in C. elegans in the Absence of Temperature Increase

Abstract: Summary Background Cellular mechanisms aimed at repairing protein damage and maintaining homeostasis, widely understood to be triggered by the damage itself, have recently been shown to be under cell nonautonomous control in the metazoan C. elegans. The heat shock response (HSR) is one such conserved mechanism, activated by cells upon exposure to proteotoxic conditions such as heat. Previously, we had shown that this conserved cytoprotective response is regulated by the thermosensory neuronal circuitry of C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
178
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(196 citation statements)
references
References 53 publications
4
178
0
1
Order By: Relevance
“…Using C. elegans expressing a single integrated copy of HSF-1 C-terminally tagged with GFP, we found that consistent with previous reports (Morton and Lamitina, 2013; Tatum et al, 2015), HSF-1 is constitutively nuclear and forms foci upon heat shock (Figures 3B, S3A and B). However, no gross change in the levels of nuclear HSF-1 where observed at day 2 of adulthood (Figures 3B).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Using C. elegans expressing a single integrated copy of HSF-1 C-terminally tagged with GFP, we found that consistent with previous reports (Morton and Lamitina, 2013; Tatum et al, 2015), HSF-1 is constitutively nuclear and forms foci upon heat shock (Figures 3B, S3A and B). However, no gross change in the levels of nuclear HSF-1 where observed at day 2 of adulthood (Figures 3B).…”
Section: Resultssupporting
confidence: 91%
“…Following washing and elution DNA was recovered using Qiagen PCR purification kit as per manufacturer's instructions. Strain OG497 was used for HSF-1 ChIP to minimize signal from the germ line (Morton and Lamitina, 2013; Tatum et al, 2015). A complete list of primers and antibodies used in these experiments can be found in supplementary tables 1 and 2.…”
Section: Methodsmentioning
confidence: 99%
“…For example, at the neuromuscular junction, cholinergic neurotransmission induces a cascade of calcium signaling events that activate HSF1 in post-synaptic muscle cells (Silva et al 2013). Similarly, in a remarkable in vivo study in non-heat-stressed C. elegans, stimulation of the worms' thermo-sensory neurons activated HSF1 in distal tissues (the pharyngeal muscles) (Tatum et al 2015). Rho family GTPases like Rac 1 also activate HSF1 (Han et al 2001;Gungor et al 2014) and play a role in formation of the synaptic spine cytoskeleton (Evans et al 2015).…”
Section: Pathways Of Hsf1 Activationmentioning
confidence: 98%
“…In particular, serotonin, an HSF1 activator (Tatum et al 2015), is associated with danger recognition (Christianson et al 2010). Oxytocin levels surge during sexual encounters (Blaicher et al 1999) and are also associated with activation of HSPs (Moghimian et al 2014).…”
Section: Hsf1 Inducers and Cognitive Preservationmentioning
confidence: 99%
“…These findings indicate that the HSR is regulated at the organismal level by neuron-to-soma signaling. Serotonin is involved in this communication mechanism (Tatum et al 2015), which not only activates the HSR but also modulates proteotoxicity in distal tissues (Prahlad and Morimoto 2011;TeixeiraCastro et al 2015). The HSR activating network involves additional types of neurons.…”
Section: Protein Quality Control At the Organismal Levelmentioning
confidence: 99%